El Aprendizaje Móvil en Educación Superior: Una Experiencia desde la Formación de Ingenieros - Ballesteros-Ballesteros, Vladimir Alfonso; Rodríguez-Cardoso, Óscar Iván; Lozano-Forero, Sébastien; Nisperuza-Toledo, Jorge Luis (Revista Científica, 2020)
This article presents the results of a research project performed at the Faculty of Engineering and Basic Sciences of the Fundación Universitaria Los Libertadores, Bogotá., whose objective was to describe the effects and experiences of incorporating the GeoGebra “Graphing Calculator” app on learning the notion of limit from the integration of mobile devices in the classroom. A sequential explanatory design was used in order to judge the hypothesis linking a positive influence of the use of smartphones and tablets and academic performance. In the quantitative stage, an experimental design of four Solomon groups was carried out and during the qualitative stage, an attitudinal test was applied and semi-structured interviews were carried out with students who participated in the treatment with the mobile application. The results obtained in the postest by the experimental groups surpassed those obtained by the control groups that participated in an intervention based on traditional teaching resources. The students who received the experimental treatment showed greater interest and motivation for learning about the topic addressed, so it can be inferred that the integration of mobile devices in the classroom promotes other innovative ways of learning calculus.